The mechanism of a gear change in the reducer - Y. V. Remizovich (Вестник СибАДИ)
This article discusses the issues related to the problem of the development of a gearbox with variable gear ratio. As a prototype adopted gear shift (CAT) vehicles. Noted the complexity of the gear shift mechanism data CAT. Proved the mechanism of a gear change, the current regardless of the direction of rotation of the drive wheel.